Characteristics of fungi contaminant in tissue culture of Bromheadia finlaysoniana (Lind.) Miq - Andriani, Desta Desta; Heriansyah, Pebra (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
Generative propagation of orchid plants has problems because orchid seeds do not have endosperm that need to be multiplied using tissue culture. Contamination is a limiting factor in the multiplication of plants in tissue culture. This study describes the types of contaminants found in Bromheadia finlaysoniana callus. This research was carried out in two stages. The first stage is carried out culture of various explants of Bromheadia finlaysoniana using murashige and Skoog media with enrichment of hormone Benzylaminopurine 1 mg/l; (Naphthalene acetic acid) 0.5 mg/l; 100 mg mynositol; pyridoxine-HCl 0.5 mg/l; thiamine-HCl 0.1 mg/l; nicotinic-acid 0.5 mg/l; glycine 2 mg/l. The second stage is observed and the percentage of contaminant fungi. The observed contaminants character includes the colour, the direction of growth, and the hyphae colony's shape. Determination of contaminants type compared to the morphology of references. The result is the highest contamination in flower stalk explants, 81%; most colonies on leaf explants are 28. Contaminant fungi grow predominantly of fungi with white and grey colour and a rough surface shape. The macroscopic character of contaminant fungi in tissue cultures mostly comes from the class of Deuteromycetes and Zygomycetes.Keywords: Bromheadia finlaysoniana , contaminant, fungi, tissue culture